5a+2b+3a-b=

Simple and best practice solution for 5a+2b+3a-b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+2b+3a-b= equation:


Simplifying
5a + 2b + 3a + -1b = 0

Reorder the terms:
5a + 3a + 2b + -1b = 0

Combine like terms: 5a + 3a = 8a
8a + 2b + -1b = 0

Combine like terms: 2b + -1b = 1b
8a + 1b = 0

Solving
8a + 1b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1b' to each side of the equation.
8a + 1b + -1b = 0 + -1b

Combine like terms: 1b + -1b = 0
8a + 0 = 0 + -1b
8a = 0 + -1b
Remove the zero:
8a = -1b

Divide each side by '8'.
a = -0.125b

Simplifying
a = -0.125b

See similar equations:

| 7x-12x-5=-43+15 | | 4(a-6)+10=2(a-5) | | 4xsquared+3=0 | | 10-1/4(8x-12)1/2(2x-4) | | 0.9x-0.7(3-x)=5.1 | | .25(98)+.75(94)= | | 15x+20y=24x+46y | | 4w^3-5w^2-8w+10=0 | | g(x)=x^3-6x^2+16 | | 1-4x/5=9 | | 3-3(4w-3)+w= | | 2x+17=75 | | 3g+20=20g+2 | | 2g+20=20g+2 | | -a=-P+3b+4c | | 3h+3=7h-17 | | 5d+6=4d+12 | | 9/4÷3/8= | | 13c/4d/2c | | 9/4÷3/8 | | 3b-7=5b-23 | | 7x+1-3(x+1)=9x+2 | | 18v^6w^9-12vw^6x^2=0 | | 3(6+2x)=3x+6 | | 7-3(x-2)=7-x(4-4x) | | 57/95=18/x | | (8z-6)=90 | | 2n+3=113 | | 4x+6x+7y+9y= | | 4x+19+3x+2=90 | | 4x+19+3x+2=180 | | 0.3/Q |

Equations solver categories